INTEGRATIVE APPROACH AND PEDAGOGICAL BASIS FOR THE USE OF INTERDISCIPLINARY CONNECTIVITY IN TEACHING - Baratov Fayzullo Shukurovich (Journals Park Publishing, 2023)
In today's educational era, interest in integration has increased due to the acceleration of scientific and technological development, the strengthening of integrative functions in the development of science, education, politics, manufacturing, and technology. Simultaneous conduct of education and training in Oriental countries is also integrated. The integration process (Latin integratio) is the integration of previously separated parts and elements of the system into a single integrity, depending on their interrelationship and complementaryity.
Keywords: integrated functions, interdisciplinary connections, student creativity, (1) meaningful; 2) operational; 3) methodological; 4) Organizational 3, mathematics of engineers.